Cadaveric study on Facial Artery Perforator Flaps - Anjali Aggarwal DaisySahni, Richa Gupta, a Sunil Gaba Tulika Gupta Harjeet Kaur (International Journal of Scientific Research and Management (IJSRM), 2017)
Head and neck reconstruction therefore presents unique challenges to the reconstructive surgeon. Fueled by the knowledge thatsingle perforators in other parts of the body have been shown to supply large areas of tissue (6), it was hypothesized that singleperforators of the facial artery would do the same for large areas of facial skin.However, a poor understanding of the number anddistribution of the perforating branches of the FA, limits wide acceptance of this approach.In this study, dissections wereperformed on 32 cadaveric hemifaces in fresh cadavers in the department of Anatomy, PGIMER, Chandigarh.The total length offacial arteries from origin to the level of the nasal alar rim was on average 182.78 ± 20.3 mm, ranging from 142.06 mm – 223.5mm. The corresponding mean diameter of FA was 2.39 ± 0.84 mm (range 1.22 – 3.57 mm). We found multiple facial arteryperforators arising from each facial artery. The average number of facial artery perforators, which were more than 0.5 mm, werefound to be 6 per facial artery (3 - 9).Maximum number of perforators wereobserved in the nasolabial area, about 13.5 mm to 23mm from the oral commissure. This study improves our understanding of facial vascularization, and shows that FAP flaps are aviable and valuable addition to the reconstructive techniques available to the plastic surgeon.